The Building Nutritious Food Baskets Project ‘Insights from the Field’ - Mulongo, G.; Maru, J.; Munyua, H.M.; Kasuga, R.; Olapeju, P.; Wende, M.; Rubyogo, Jean-Claude; Gethi, J. (International Potato Center, 2018)
This booklet is a compilation of insights and success stories from the field during the implementation of the Building Nutritious Food Baskets (BNFB) project; a three-year project (November 2015 to October 2018) implemented in Nigeria and Tanzania and funded by the Bill & Melinda Gates Foundation. The objective of compiling these insights and success stories is to showcase and highlight BNFB’s experiences and interactions with various stakeholders during implementation, highlight successful partnerships and to provide a ‘human touch’ in narrating the process and how the project was able to deliver results, outcomes and the emerging impact of these efforts.